Banks' loans to reduce the risk of leasing lines - Nozimov Eldor Anvarovich (Indonesian Journal of Innovation Studies, 2020)
In this article, theoretical views on leasing lending, improving lending practices and ways to reduce risks, as well as current problems and their practical solutions and prospects for future development will be widely considered.